2000
DOI: 10.1063/1.481449
|View full text |Cite
|
Sign up to set email alerts
|

Multiple lines of conical intersections and nondegenerate ground state in T⊗t2 Jahn–Teller systems

Abstract: We have investigated the T⊗t2 Jahn–Teller problem with linear and quadratic vibronic coupling including a fourth-order term. First, numerical calculations of the lowest vibronic states were carried out by direct diagonalization of the Hamiltonian. The results show that the energy level of the ground vibronic state, which is triply degenerate T for small quadratic coupling g values, intersects the next A level with increasing g, thus realizing the nondegenerate ground state at sufficiently large g values. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 18 publications
0
32
0
Order By: Relevance
“…They showed that, contrary to what had been widely thought before, the ground state may be either a vibronic doublet or a singlet, depending on the distance (which is a function of the parameters in the vibronic Hamiltonian) of these trigonal ci's from the centre. (A similar instance of "quantum phase transition" was noted for a threefold degenerate system in [275] and, earlier, for an icosahedral system, in [276]). …”
Section: Non-linearities That Lead To Multiple Degeneraciesmentioning
confidence: 91%
“…They showed that, contrary to what had been widely thought before, the ground state may be either a vibronic doublet or a singlet, depending on the distance (which is a function of the parameters in the vibronic Hamiltonian) of these trigonal ci's from the centre. (A similar instance of "quantum phase transition" was noted for a threefold degenerate system in [275] and, earlier, for an icosahedral system, in [276]). …”
Section: Non-linearities That Lead To Multiple Degeneraciesmentioning
confidence: 91%
“…More than two states may also interact in this manner. For example, the T × τ Jahn-Teller effect, where a triply degenerate electronic state is split by a triply degenerate molecular vibration, can be analyzed in the same way (47). Some other important cases, such as -coupling in linear molecules and pseudo-JahnTeller coupling, are described in Section 4.…”
Section: Classification Of Conical Intersectionsmentioning
confidence: 98%
“…11 In the T t 2 problem sufficiently strong quadratic terms lead to additional seams of conical intersections that change the ground state degeneracy too. 12 Important results obtained with strong quadratic coupling terms raise the question of the role of higher order terms and the convergence of the vibronic coupling approach taken in consecutive approximations. To explore this issue we begin with cubic terms of the vibronic coupling.…”
Section: Introductionmentioning
confidence: 99%